Concurrent enhancement of provitamin A and yield in tropical maize hybrids - Menkir, Abebe; Dieng, Ibnou; Meseka, Silvestro; Maziya-Dixon, Bussie; Bossey, Bunmi; Muhyideen, Oyekunle; Ewool, Manfred; Coulibaly, Mmadou; Mengesha, Wende (Frontiers in Plant Science, 2025)
Maize is a strategic food crop in sub-Saharan Africa, where vitamin A deficiency affects millions. Significant investments have thus focused on developing maize varieties that provide 50% of the daily vitamin A requirement for vulnerable populations. Despite the release of many provitamin A enriched maize varieties across Africa, estimates of genetic gains in provitamin A content and grain yield from long-term breeding programs are undocumented. This study analyzed data from 124 provitamin A-enriched hybrids and eight commercial checks recorded over 12 years across diverse environments to estimate genetic gains. Results showed a significant annual increase of 2.05% in provitamin A and 3.54% in β-carotene, alongside a 1.09% reduction in β-cryptoxanthin. Additionally, our breeding program achieved an annual genetic gain of 1.88% in grain yield while simultaneously decreasing silking days by 0.09% and plant aspect score by 0.35%, alongside a 0.31% increase in plant height. We identified 23 hybrids that accumulated 54% to 95% more provitamin A and produced 10% to 30% higher grain yields compared to the best commercial hybrid (COMYH129). These findings demonstrate concurrent genetic gains in both provitamin A content and grain yield, highlighting the potential for further productivity increase and accumulation of beneficial carotenoid to improve human health.